Alcohol and Cannabinoids Differentially Affect HIV Infection and Function of Human Monocyte-Derived Dendritic Cells (MDDC) - Agudelo, Marisela; Figueroa, Gloria; Yndart, Adriana; Casteleiro, Gianna; Muñoz, Karla; Samikkannu, Thangavel; Atluri, Venkata; Nair, Madhavan P. (Frontiers in Microbiology, 2015)
During human immunodeficiency virus (HIV) infection, alcohol has been known to induce inflammation while cannabinoids have been shown to have an anti-inflammatory role. For instance cannabinoids have been shown to reduce susceptibility to HIV-1 infection and attenuate HIV replication in macrophages. Recently, we demonstrated that alcohol induces cannabinoid receptors and regulates cytokine production by monocyte-derived dendritic cells (MDDC). However, the ability of alcohol and cannabinoids to alter MDDC function during HIV infection has not been clearly elucidated yet. In order to study the potential impact of alcohol and cannabinoids on differentiated MDDC infected with HIV, monocytes were cultured for 7 days with GM-CSF and IL-4, differentiated MDDC were infected with HIV-1Ba-L and treated with EtOH (0.1 and 0.2%), THC (5 and 10 uM), or JWH-015 (5 and 10 uM) for 4-7 days. HIV infection of MDDC was confirmed by p24 and Long Terminal Repeats (LTR) estimation. MDDC endocytosis assay and cytokine array profiles were measured to investigate the effects of HIV and substances of abuse on MDDC function. Our results show the HIV+EtOH treated MDDC had the highest levels of p24 production and expression when compared with the HIV positive controls and the cannabinoid treated cells. Although both cannabinoids, THC and JWH-015 had lower levels of p24 production and expression, the HIV+JWH-015 treated MDDC had the lowest levels of p24 when compared to the HIV+THC treated cells. In addition, MDDC endocytic function and cytokine production were also differentially altered after alcohol and cannabinoid treatments. Our results show a differential effect of alcohol and cannabinoids, which may provide insights into the divergent inflammatory role of alcohol and cannabinoids to modulate MDDC function in the context of HIV infection.